Numerical Analysis for a Realistic Support Design: Case Study of the Komurhan Tunnel in Eastern Turkey - Yalcin, Erkut; Gurocak, Zulfu; Ghabchi, Rouzbeh; Zaman, Musharraf (Asce-Amer Soc Civil Engineers, 2016)
The aim of this study was to highlight the importance of the numerical approach in realistic support design for tunneling. The Komurhan Tunnel, which is to be constructed between the Elazig-Malatya highway, located east of Elazig City in eastern Turkey, was selected as the application site of this study. The lithology of this area consists of Late Cretaceous-age ophiolitic rocks, known as Komurhan ophiolites. Field and laboratory studies were performed to determine the geotechnical properties of rock mass and intact rock materials. Empirical and numerical approaches were used, and the results were compared, focusing on tunnel design safety. The rock mass was classified in terms of the rock mass rating (RMR), rock mass index (RMi), Austrian tunneling method, and geological strength index rock mass classification systems, and then the support systems for the tunnel were determined accordingly. The support systems obtained from the classification systems were also analyzed using software based on the FEM. On the basis of the numerical analysis, a more reliable and safe support design was recommended. The results show that the support systems suggested by the RMi method were not sufficient for the walls; however, the support systems were found to be safe for the crowns. Furthermore, the support systems suggested by the RMR system did not provide enough stability for both walls and crowns. The support system recommended in this study reduced the thickness of the plastic zone and total displacement values. (C) 2015 American Society of Civil Engineers.
Keywords: Empirical approach; Finite-element method; Numerical approach; Rock mass classification; Tunneling